Fatigue failure mechanisms and life prediction of additive manufactured metallic lattices: a comprehensive review - Hao Xin; Dingcheng Tang; Linwei Dang; Lei Gao; Zhenyu Yang; Bin Wu; Xiaofan He; Zhixin Zhan (Virtual and Physical Prototyping)
In recent years, expanding application scenarios have imposed higher demands on the geometric design and performance of metallic structures. Additive manufacturing (AM) has become essential for producing complex, customised geometries. Metallic lattice materials, known for their periodic structural arrangements, offer lightweight solutions ideal for high-strength applications like aerospace. However, during long-term use, these structures are often subjected to cyclic loading, making fatigue resistance a critical property. The complexity of fatigue-related challenges necessitates thorough research to fully understand the fatigue behaviours of these materials. This paper adopts a standard research approach to explore fatigue issues, with a focus on AM metallic lattice materials. It reviews common manufacturing methods and post-processing techniques, with particular emphasis on the unique process-induced defects found in lattice structures. The study also delves into the fatigue behaviours influenced by specific configurations and loading conditions, categorises the factors impacting fatigue failure in lattice materials, and presents a comprehensive review of fatigue life prediction methods, derived from an enhanced understanding of the fatigue process and the development of progressive fatigue failure algorithms. Finally, the current research advancements and limitations are discussed to provide a clearer perspective on the fatigue challenges associated with AM metallic lattice materials.